Kemiskinan Struktural Akibat dari Tidak Berjalannya Fungsi Pemerintahan Secara Maksimal di Daerah Istimewa Yogyakarta - Pawit Fadila Rika Farisa; Riefda Nardi Maharani; Nurrachma Maharani; Tantri Nur Aditya Siswanto; Winda Dwiastuti; Azzahra Nurrachman; Mulyadi Mulyadi (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
The application of the principles of good governance such as accountability, transparency and law enforcement in limiting poverty requires several supporting factors in eradicating poverty which in this study took place in the Yogyakarta region while the approach to this problem uses empirical normative studies which through actions or behaviors that occur in the community so that it can be used to answer the formulation of the problem which will be able to conclude the root of the problems that occur especially in the area or the Yogyakarta region.